Hadith #37 - Sahih Muslim - Suh'aib bin Harb شعيب بن حرب (Sahih Muslim)
I heard the Messenger of Allah (ﷺ) say: He who professed that there is no god but Allah and made a denial of everything which the people worship beside Allah, his property and blood became inviolable, an their affairs rest with Allah.
Grade: Sahih

Hadith #48 - Sahih Muslim - Suh'aib bin Harb شعيب بن حرب (Sahih Muslim)
Allah would make him (he who affirms these truths) enter Paradise through one of the eight doors which he would like.
Grade: Sahih

Hadith #354 - Sahih Muslim - Suh'aib bin Harb شعيب بن حرب (Sahih Muslim)
When those deserving of Paradise would enter Paradise, the Blessed and the Exalted would ask: Do you wish Me to give you anything more? They would say: Hast Thou not brightened our faces? Hast Thou not made us enter Paradise and saved us from Fire? He (the narrator) said: He (God) would lift the veil, and of things given to them nothing would he dearer to them than the sight of their Lord, the Mighty and the Glorious.
Grade: Sahih

Hadith #7314 - Sahih Muslim - Suh'aib bin Harb شعيب بن حرب (Sahih Muslim)
Strange are the ways of a believer for there is good in every affair of his and this is not the case with anyone else except in the case of a believer for if he has an occasion to feel delight, he thanks (God), thus there is a good for him in it, and if he gets into trouble and shows resignation (and endures it patiently), there is a good for him in it.
Grade: Sahih

Hadith #7325 - Sahih Muslim - Suh'aib bin Harb شعيب بن حرب (Sahih Muslim)
There lived a king before you and he had a (court) magician. As he (the magician) grew old, he said to the king: I have grown old, send some young boy to me so that I should teach him magic. He (the king) sent to him a young man so that he should train him (in magic). And on his way (to the magician) he (the young man) found a monk sitting there. He (the young man) listened to his (the monk’s) talk and was impressed by it. It became his habit that on his way to the magician he met the monk and
Grade: Sahih